THE INFLUENCE OF ONLINE GAMES ON THE CHARACTERISTICS OF HIGH SCHOOL STUDENTS - Naziha Andien Dalimunthe; Maria Ulfah Handayani (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2025)
Online gaming is deeply embedded in adolescent life and its effects on high-school students vary by motivation, play patterns, and context. This literature reviews current research to provide an overview of how online games influence student characteristics. Methods: independent literature searches were conducted across PubMed, and Google Scholar using literatures from at least 2020 on gaming addiction result based on several points: the potential for cognitive and social development, including enhanced problem-solving skills and the formation of robust online communities, the adverse impacts on academic performance and personal discipline, largely attributed to the displacement of study time and the intricate relationship with mental health, where gaming can serve as both a coping mechanism for stress and a contributor to conditions like depression and anxiety. Evidence suggests potential cognitive and socio-emotional gains alongside risks when play becomes compulsive, including displaced study time, sleep loss, and associations with depressive and anxiety symptoms.